Gender, Wages, and Social Security in Chinas Industrial Sector - Johanna Rickne (Research Institute of Industrial Economics (IFN), 2010)
This study compares average earnings and productivities for men and women employed in roughly 200,000 Chinese industrial enterprises. Womens average wages lag behind mens wages by 11%, and this result is robust to the inclusion of non-wage income in the form of social insurance payments. The gender-wage gap is wider among workers with more than 12 years of education (28%), mainly because of the higher relative wages received by skilled men in foreign-invested firms. Womens average productivity falls behind mens productivity by a larger margin than the gap in earnings, and the null-hypothesis of earnings discrimination is thereby rejected. Equal average wages between men and women are found among firms located in Chinas Special Economic Zones, and also among some light industrial sectors with high shares of female employees. Market reform hence appears to have improved womens relative incomes.
Keywords: I30; J16; J71; O10; 330; China; Gender Wage Gap; Non-wage Compensation; Fraueneinkommen; Betriebliche Sozialleistungen; Geschlechterdiskriminierung; Industrie; China